ФОРМУВАННЯ ПІЗНАВАЛЬНОЇ САМОСТІЙНОСТІ СТУДЕНТІВ ЕКОНОМІЧНОГО НАПРЯМУ ПІДГОТОВКИ В ПРОЦЕСІ ВИВЧЕННЯ ФАХОВИХ ДИСЦИПЛІН (Педагогіка вищої та середньої школи, 2022)
The article deals with some actual problems concerning the formation o f students’ (are being trained to be economists) cognitive self directed activities in the process o f special disciplines studies.